Ambulatory blood pressure monitoring profile in stroke hypertensive patient: death associative parameters - Zhemanyuk, S. P.; Жеманюк, Світлана Павлівна (Vienna, 2017)
Hypertension is one of the crucial heath problem among Ukrainian population which increases of mortality from cardiovascular diseases 1. Moreover, hypertension plays a causative role in the pathogenesis of stroke. The association between BP and stroke mortality is strong and direct 2. Clinical trials have unequivocally demonstrated that BP lowering in people with hypertension reduces stroke risk. It has been reported that ABPM is superior predictor of future cardiovascular events than clinic BP 3.
Keywords: ischemic stroke; hypertension; ambulatory arterial stiffness index; symmetric slope; symmetric ambulatory arterial stiffness index